2005
DOI: 10.1158/0008-5472.can-03-3675
|View full text |Cite
|
Sign up to set email alerts
|

Human Splicing Factor SPF45 (RBM17) Confers Broad Multidrug Resistance to Anticancer Drugs When Overexpressed— a Phenotype Partially Reversed By Selective Estrogen Receptor Modulators

Abstract: The splicing factor SPF45 (RBM17) is frequently overexpressed in many solid tumors, and stable expression in HeLa cells confers resistance to doxorubicin and vincristine. In this study, we characterized stable transfectants of A2780 ovarian carcinoma cells. In a 3-day cytotoxicity assay, human SPF45 overexpression conferred 3-to 21-fold resistance to carboplatin, vinorelbine, doxorubicin, etoposide, mitoxantrone, and vincristine. In addition, resistance to gemcitabine and pemetrexed was observed at the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…While studies directly investigating whether the vertebrate SPF45 protein also functions in DNA repair have not been carried out, recent gain-of-function and loss-of-function studies in human cancer–cell lines are suggestive. In these studies, a reduction in SPF45 expression in A2780 cells, an ovarian carcinoma cell line, resulted in chemotherapeutic drug sensitivity [36]. Conversely, ectopic overexpression of SPF45 in both A2780 cells and HeLa cells rendered the cells resistant to several different anticancer drugs [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…While studies directly investigating whether the vertebrate SPF45 protein also functions in DNA repair have not been carried out, recent gain-of-function and loss-of-function studies in human cancer–cell lines are suggestive. In these studies, a reduction in SPF45 expression in A2780 cells, an ovarian carcinoma cell line, resulted in chemotherapeutic drug sensitivity [36]. Conversely, ectopic overexpression of SPF45 in both A2780 cells and HeLa cells rendered the cells resistant to several different anticancer drugs [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Multicellular spheroids of cancer cells often have intrinsically higher drug resistance properties than the same cells grown in culture (18), and ovarian cancer is characterized by peritoneal ascites containing multicellular spheroids, which serve as a reservoir of drugresistant and metastatic cells. SPF45 overexpression has been reported to induce multidrug resistance in both A2780 ovarian cancer (48) and HeLa cervical cancer (50) cell lines grown in monolayers, and the effect in spheroids is unknown. Therefore, SPF45 upregulation of fibronectin expression may have a more pronounced effect in spheroids and, indeed, we have observed a significant overexpression of SPF45 in primary ovarian cancer cells from patient ascites (Y. Liu, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, SPF45 expression is low in most normal tissues but is overexpressed in breast, ovarian, bladder, and prostate cancer (50). Ectopic overexpression of SPF45 in HeLa cervical cancer (50) and A2780 ovarian cancer (48) cell lines induced a multidrug-resistant phenotype, while knockdown of endogenous SPF45 sensitized A2780 cells to etoposide (48).…”
mentioning
confidence: 99%
“…To date, there have been limited reports associating aberrant splicing with drug resistance phenomena. For instance, Perry et al 31 have shown that human splicing factor SPF45 (RBM17), which is frequently overexpressed in various solid tumors, confers multidrug resistance (MDR) to anticancer drugs including doxorubicin and the antifolate pemetrexed upon ectopic overexpression of SPF45 in HeLa cells. More recently, Corsini et al 32 suggested that the molecular mechanism underlying MDR in these cells is alternative splicing of FAS, a proapoptotic factor.…”
Section: Discussionmentioning
confidence: 99%